Online Self-Presentation and Braggadocian Behavior in Millennials (Journal of Social and Industrial Psychology, 2023)
Social media is a form of technological development that gives rise to a new behavior called braggadocios behavior, which is often characterized by always uploading status/tweets to show how cool and famous someone is. In addition, social media is one of the new social platforms where someone will try to create their desired impression, which is called, online self-presentation. The millennial is the generation that is most familiar with social media. Because they like the form of interaction in it. The purpose of this research is to find out the relationship between online self-presentation and braggadocios behavior in the millennial generation. This study is using a quantitative method with correlational analysis. The research subjects are Semarang State University students spread across the Faculty of Education, Faculty of Economics, Faculty of Languages ​​and Arts, and the Faculty of Law with a total of 347 subjects. Spearman Rho is used to analyze data that were collected. The results showed that the hypothesis can be accepted, with a correlation coefficient (r) of 0.853 with a significance level of 0.000. This means that there is a positive relationship between online self-presentation and braggadocios behavior in the millennial generation. The bridging aspect between both variables is multiple identities, which consist of the identity from birth (ethnicity, religion, and gender) and artificial identity. Media users will emphasize artificial identity and make it an ideal self.